PENGARUH REWARD DAN PUNISHMENT TERHADAP KINERJA KARYAWAN PADA PT SUKSES MITRA SEJAHTERA - Kristanti, Desi; Rahayu, Budi; Fikriyah, Amin Lailatul; Maeswanto (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine the effect of reward and punishment on employee performance at PT Sukses Mitra Sejahtera. And to find out which variable has the most influence on employee performance. The research was conducted using a survey method, where data was obtained by distributing questionnaires to 60 respondents. The population in this study were all employees of PT Sukses Mitra Sejahtera. The sampling method used is non-probability sampling, the data obtained is then analyzed using the classical assumption test, multiple linear regression analysis, determination test consisting of t and f tests. The results of testing the hypothesis partially prove that there is an influence between rewards on employee performance. through the calculation results obtained a coefficient value of 0.469 and t count of 3.175 with a significant value of 0.002 results greater than 0.05. The results of testing the hypothesis partially prove that there is an influence between punishment on employee performance. through the calculation results obtained a coefficient value of 0.569 and t count of 4.412 with a significant result value of 0.000 greater than 0.05. This means that there is an influence between the reward and punishment variables on employee performance at PT Sukses Mitra Sejahtera.